Ayat Muhkamat dan Ayat Mutasyabihat: Tinjauan Sumber Hukum Ekonomi Islam - Yusraini, Yusraini; Hasan, Mustofa; Ishandawi, Ishandawi (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
The importance of understanding and studying the sources of Islamic law is the main basis for Muslims in living their lives from time to time. The Koran is the highest source of law which is the main reference in determining Islamic law. The Koran contains more than six thousand verses, collected in one hundred and fourteen suras. Among the verses of the Koran there are what are called muhkamat verses and mutasyabihat verses. One aspect that needs to be considered is the difference between muhkamat and mutasyabihat verses in the Koran. Muhkamat verses are verses whose meaning is clear, namely verses other than mutasyabihat verses. The muhkamat verses explain something and give details, whether it is forbidden or lawful, regarding good promises or bad promises, regarding reward or punishment, warnings or prohibitions, whether they contain news or i'tibar advice or similes or something similar, all of them This is explained in detail and clearly. As for the existence of the mutasyabihat verse, even though it has a wealth of meaning, the translation is carried out by considering the context and hadith.